1991
DOI: 10.1136/hrt.65.1.37
|View full text |Cite
|
Sign up to set email alerts
|

End diastolic flow velocity just beneath the aortic isthmus assessed by pulsed Doppler echocardiography: a new predictor of the aortic regurgitant fraction.

Abstract: End diastolic flow velocity just beneath the aortic isthmus was measured within 72 hours of cardiac catheterisation by pulsed Doppler echocardiography in 30 controls and 61 patients with aortic regurgitation. The end diastolic flow velocity was determined at the peak R wave on a simultaneously recorded electrocardiogram. In all controls there was no reverse flow at the end diastole beneath the aortic isthmus. In patients with aortic regurgitation the end diastolic flow velocity correlated well with the angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 9 publications
3
30
0
Order By: Relevance
“…Furthermore, none of the included subjects had holo-diastolic reversal, with an extremely high reverse flow in end diastole (Table), which is strongly suggestive of aortic regurgitation. 19,33 Despite the established absence of aortic regurgitation, the presence of aortic flow reversal was confirmed in 100% of our subjects, suggesting that other mechanisms rather than aortic valve disorder are primarily involved in the generation of aortic reverse flow. We found that the aortic reverse/forward flow ratio was independently associated with aortic characteristic impedance and PWV (Figure 2; Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, none of the included subjects had holo-diastolic reversal, with an extremely high reverse flow in end diastole (Table), which is strongly suggestive of aortic regurgitation. 19,33 Despite the established absence of aortic regurgitation, the presence of aortic flow reversal was confirmed in 100% of our subjects, suggesting that other mechanisms rather than aortic valve disorder are primarily involved in the generation of aortic reverse flow. We found that the aortic reverse/forward flow ratio was independently associated with aortic characteristic impedance and PWV (Figure 2; Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic regurgitation was assessed echocardiographically as trivial, mild (regurgitation without a reverse diastolic flow in the aortic arch), moderate (reverse diastolic flow in the aortic arch but not in the abdominal aorta), or severe (reverse diastolic flow in the abdominal aorta). 19 If applicable, aortic regurgitation shortly before subsequent aortic valve surgery also was evaluated.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…According to Pearson correlation analysis their correlation was very significant (r=0.69, p<0.001). Previous studies showed that forward and reverse flow profiles in the ascending aorta can be irregular and unreliable (12,13). However, there are other studies showing that descending aorta velocity profile was more reliable (14,15).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have reported a good correlation between severity of aortic regurgitation and Doppler assessment of flow velocity at the end of diastole in the descending aorta just beneath the aortic isthmus (11)(12)(13)(14). Also descending aorta velocity profile was more reliable than ascending aorta (15).…”
Section: Introductionmentioning
confidence: 81%